2009
DOI: 10.1093/molehr/gap032
|View full text |Cite
|
Sign up to set email alerts
|

ROCK2 allelic variants are not associated with pre-eclampsia susceptibility in the Finnish population

Abstract: The rho-associated coiled-coil protein kinase 2 (ROCK2) gene has been suggested to associate with general hypertension and is therefore a plausible functional candidate gene for pre-eclampsia. ROCK2 maps to chromosome 2p25, which we have implicated previously in a linkage study of pre-eclampsia. We have re-sequenced exons and putative promoter region of ROCK2 in up to 30 pre-eclampsia patients and 22 controls and genotyped putative functional single-nucleotide polymorphisms (SNPs) as well as tagging SNPs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The target for miR-135b predicted by the miRDB database corresponds to rho-associated coiled-coil protein kinase 2 ( ROCK2 ) known to be elevated in PE placentas ( 46 ). ROCK2 has been mapped within the PE linkage peak on chromosome 2p25 in genome-wide linkage screening ( 47 ). miR-135b is expressed in placenta tissue and found in the maternal circulation ( 48 ), confirming its feasible functional significance in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The target for miR-135b predicted by the miRDB database corresponds to rho-associated coiled-coil protein kinase 2 ( ROCK2 ) known to be elevated in PE placentas ( 46 ). ROCK2 has been mapped within the PE linkage peak on chromosome 2p25 in genome-wide linkage screening ( 47 ). miR-135b is expressed in placenta tissue and found in the maternal circulation ( 48 ), confirming its feasible functional significance in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, inhibition of ROCK2 by certain medical agents led to normotension [ 20 , 21 ]. Peterson et al [ 22 ] evaluated allelic variant of ROCK2 in women with preeclempsia and proposed that ROCK2 could be a functional target for the regulation of preeclempsia. We detected two homozygote and one heterozygote genotypes for ROCK2 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that syncytiotrophoblast cells of the placenta express ROCK2 and expression is up regulated in pre-eclampsia 77. A study examining ten polymorphisms within ROCK2 failed to detect any association with pre-eclampsia 78. This study was powered only to detect a genetic effect of 1.6, and a larger study is warranted to investigate both ROCK2 and other genes at the 2p25 locus.…”
Section: Genome-wide Screeningmentioning
confidence: 92%